2022
DOI: 10.1111/jam.15449
|View full text |Cite
|
Sign up to set email alerts
|

Membrane vesicles from antibiotic-resistant Staphylococcus aureus transfer antibiotic-resistance to antibiotic-susceptible Escherichia coli

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 64 publications
(103 reference statements)
0
10
0
Order By: Relevance
“…aureus (MRSA) also utilize β-lactamases to degrade β-lactam antibiotics, thereby safeguarding E . coli [ 51 ].…”
Section: Bacterial Evs Contribute To Antimicrobial Resistancementioning
confidence: 99%
“…aureus (MRSA) also utilize β-lactamases to degrade β-lactam antibiotics, thereby safeguarding E . coli [ 51 ].…”
Section: Bacterial Evs Contribute To Antimicrobial Resistancementioning
confidence: 99%
“…Bacterial membrane vesicles carry lipids, proteins, and DNA that can be released to the external environment under stressful conditions, fuse, and transform other bacteria [29]. Recently, Lee and colleagues showed that membrane vesicle fusion could transfer β-lactam resistance substances from S. aureus (MRSA strain) to E. coli, resulting in increased β-lactamase activity and conferring resistance to β-lactam antibiotics [30].…”
Section: Horizontal Gene Transfermentioning
confidence: 99%
“…Antibiotics are a great invention. Since the discovery of penicillin, antibiotics have saved countless lives [ 34 ]. However, with the misuse of antibiotics, bacterial resistance has caused increasingly serious problems [ 35 ].…”
Section: Approaches To Enhance Antibacterial Potentialmentioning
confidence: 99%